Reading Promotion as Ideology: The Reproduction of Power Relations in Book Reading Meetings by the Iran Public Libraries Foundation - Alireza Panahi Dodaran; Mohammad Khandan; Majid Soleimani Sasani (کتابداری و اطلاع‌رسانی)
Objective: This study aims to identify the ideological dimensions of reading promotion and to explore how subjectivity and practice are discursively and ideologically constructed in the "book reading meetings".Methodology: The research method is discourse analysis. The data were extracted from 21 texts related to reading promotion in the "book reading meetings", which were purposively sampled. Data analysis was conducted in MaxQDA 2020, using Fairclough’s tools for text and metatext analysis, in three levels: description, interpretation, and explanation.Findings: The "presenter" subject is capable of identifying and accessing information, knows the methods to treat and prevent illness, and is familiar with the type of illness and the information required for the treatment and prevention of the "audience" subject. In contrast, the "audience" subject which is a potential or actual patient in need of treatment or prevention through information lacks the ability to identify relevant information, the nature of their illness, and the necessary information for treatment and prevention. As a result of the application of the "presentation" genre, the "presenter" subject positions themselves at a higher level than the "audience" subject, has control over the meeting process, and manages the flow of speech and turn-taking. The "presenter" subject is predominantly the speaker and conveys and introduces information to the "audience" subject. On the other hand, the "audience" subject occupies a lower position relative to the "presenter" subject, has limited control over the meeting process, is mostly a listener, and improves or gains immunity by receiving information about their illness.Conclusion: Through the ideology of "reading promotion", the content of reading materials is represented as "information", whereas, in reality, the content of reading materials can contain both information and disinformation. The "presenter" subject is represented as the sole source of information, and the "audience" subject lacks this information; consequently, the "presenter" subject exerts dominance over the "audience" subject. The historical possibilities of the "audience" subject are disregarded. The possibility of critical engagement for the "audience" subject is rendered impossible. The transmission of disinformation, control of information, and manipulation of the "audience" subject's thoughts for the reproduction of social relations based on domination are facilitated. The social cause of what is represented as a person's illness is concealed. Although acquiring information cannot significantly affect what is represented as the person's illness, it is portrayed as if the lack of information is the cause, and that receiving information will treat and prevent the illness.